IDENTIFICATION OF HUNTETE BEACH TOURISM OBJECT IN KULATI VILLAGE EAST TOMIA SUB-DISTRICT WAKATOBI REGENCY - La Ode Amaluddin; Fahrudi Ahwan Ikhsan; Andri Estining Sejati; M Mutiana (Department of Geography Education, University of Jember, 2018)
Huntete Beach has good physical potention, but still not optimal visitors. The purposes of this paper there are two (a) to determine the potention of Huntete Beach tourism objects in Kulati Village, East Tomia Subdistrict, Wakatobi Regency, (b) To find out the perception of tourists on the potential of Huntete Beach tourism objects in Kulati Village, East Tomia District, Wakatobi Regency. This research uses survey method. The results of this paper are (a) the potential of Huntete Beach is in the medium category (internal potential) and low (external potential), so it needs to be developed again so that it can become a main tourism object in East Tomia Subdistrict, Wakatobi Regency, (b) Presumption from tourists who visit that there is a potential in Huntete Beach tourism, so needs better management by completing facilities that are not yet available. It can tourists more enjoy the natural phanorama and not feel bored at this place. Keywords: potential identification, tourism object, Huntete beach References Arida, I, N, S., Wiguna, P, P, K., Narka, I, W., dan Pebrianti N, K, O. 2017. Developmentplanningoftourist village using participatory mapping (Case study: Mambal Village,Badung Regency, Indonesia).IOP Conf. Series: Earth and Environmental Science 98012044: 1-10. Burton, Rosemary.1995.TravelGeography. London: Pitman Publishing. Culusjarvi, Outi. 2016. Resort-oriented tourism development and local tourism networks-acase study from Northern Finlan.VENNIA194 (1): 3-17 Damanik J dan Weber H.F. 2006.Perencanaan Ekowisata dari Teori ke Aplikasi.Yogyakarta: PUSPAR UGM & Penerbit Andi. Damardjati, R.S. 1995.Istilah-istilah DuniaPariwisata. Jakarta: Gramedia Pustaka Umum. Devina, 2011.Tingkat Daya Tarik Objek Wisata Pantai di Wilayah Karst Kabupaten GunungKidul. Depok: Universitas Indonesia. Hanifah dkk. 2018. Analysisof tourist travel patterns toward health care facilities(Casestudyof Prambanan Sub-District, Klaten District.Geosfera Indonesia3 (2): 1-10.LawNo. 9Year1990about Tourism. Lumbanraja, Victor. 2012. Tourismarea life cycle in lake toba.Indonesian Journal of Geography44 (2): 150-160. Lohmann, Gui, dan Pearce, D, G. 2012. Tourism and transport relationships: the suppliers’perspective in gateway destinations in New Zealand.Asia Pacific Journal of TourismResearch17(1): 14-29. Maramin. 2004.Teknik dan Aplikasi Pengambilan Keputusan Kriteria Majemuk. Jakarta:Gramedia Widiasarana Indonesia. Pearce,Douglas.1983.Toursit DevelopmentTopicsInAppliedGeography.England:LongmandGroupLimited.Pendit, Nyoman, S. 2003.Manajemen Kepariwisataan. Jakarta: Pradnya Paramitha.Pitmann, T., Broomhall, S., McEwan, J., dan Majocha, E. 2010.Adult learning in educationaltourism.Australian Journal of Adult Learning50 (2): 219-238. Prahasta, Eddy.2002.Konsep-konsep Dasar Sistem Informasi Geografis. Bandung:Informatika.Rangkuti,F. 2004.Riset Pemasaran (Edisi 2).Yogyakarta: Andi Offset. Singarimbun, Masri dan Sofian Effendi. 2008. Metode Penelitian Survei.Jakarta: LP3ES.Sugiyono, 2008.Metode Penelitian Bisnis. Bandung: Alfabeta. Sujali,1989.Geografi Pariwisata danKepariwisataan. Fakultas Geografi UGM:Yogyakarta. Sutedjo, Agus dan Murtini Sri. 2007.Geografi Pariwisata. Surabaya: Penerbit Unesa University Press Suwantoro,Gamal, 1997.Dasar-dasar Pariwisata.Yogyakarta: Andi.Suwantoro,Gamal.2004.Dasar-dasar Pariwisata.Yogyakarta: Andi. Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License